1985
DOI: 10.1677/joe.0.107r013
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Tissue Androgen Receptors in the Congenitally Obese Male Zucker Rat

Abstract: Androgen receptor (AR) concentrations were measured in the prostates and livers of the infertile congenitally obese male Zucker rat and their fertile non-obese litter-mates. In obese rats AR concentrations were significantly lower in both the liver (p less than 0.001) and the prostates (p less than 0.01) of the obese rats compared with the non-obese rats, despite similar plasma testosterone concentrations in both phenotypes. These findings suggest that a potential cause for the infertility observed in the obes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1986
1986
1989
1989

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Reduced concentrations of oestradiol receptors have been found in the uteri of obese rats (Saiduddin & Zassenhaus, 1979). Reduced concen¬ trations of androgen receptors in the prostate and liver of obese rats have also been reported (Bannister & Whitaker, 1985). The response of peripheral target tissues to gonadal steroids may, therefore, be abnor¬ mal in obese Zucker rats.…”
Section: Introductionmentioning
confidence: 94%
“…Reduced concentrations of oestradiol receptors have been found in the uteri of obese rats (Saiduddin & Zassenhaus, 1979). Reduced concen¬ trations of androgen receptors in the prostate and liver of obese rats have also been reported (Bannister & Whitaker, 1985). The response of peripheral target tissues to gonadal steroids may, therefore, be abnor¬ mal in obese Zucker rats.…”
Section: Introductionmentioning
confidence: 94%
“…The presence of reduced AR concentration in diseased liver is in broad agreement with the data from Nagasue et al (lo), who reported on hepatocellar carcinoma and the surrounding parenchyma. This is not a disease-specific process for it has been reported in experimental alcoholic liver disease (1 8), chronic active hepatitis and congenital steatosis (14). The significance of this reduction may be two-fold.…”
Section: Discussionmentioning
confidence: 91%
“…An alternative explanation is that AR levels are reduced in a non-specific manner by tissue damage and then become expressed during the process of carcinogenesis. This concept is supported by the fact that liver AR are also reduced in hepatic steatosis of either congenital (Bannister & Whitaker, 1985) or alcohol induced aetiology (Eagon et al, 1985), or in simple chronic active hepatitis without cirrhosis (Nagasue et al, 1985 oral contraceptive-associated hepatic adenoma. No studies have been performed on ER levels during the pre-malignant phase of tumour production but in a single case report ER levels were increased in focal nodular hyperplasia (Porter et al, 1983b).…”
mentioning
confidence: 93%